On the Spot Presentation-Based Assessment (OTSPA): Student Perception and Predictive Value of a Novel Summative Assessment with a Formative Assessment Flavour - Sharmini Julita Paramasivam; Yasmin Abou-Amer; Khalil Saadeh (MDPI AG, 2023)
University of Surrey's School of Veterinary Medicine introduced an assessment called On The Spot Presentation-based Assessment (OTSPA) into the 3rd and 4th year of a 5-year veterinary degree programme. The OTSPA is designed as a low-weightage summative assessment, conducted in a supportive learning environment to create a better learning experience. The OTSPA is a timed oral assessment with an 'on the spot' selection of taught topics, i.e., students prepare to be assessed on all topics but a subset is chosen on the day. The OTSPA was designed to test the students' depth of knowledge while promoting skills like communication and public speaking. The aim of this study is to describe the design and operation of the OTSPA, to evaluate student perception of the approach, and to assess the OTSPA's predictive value in relation to the final written summative assessment (FWSA), which is an indicator of academic performance. This study assessed the student perceptions (N = 98) and predictive value of the OTSPA on the FWSA in three modules: Zoological Medicine (ZM), Fundamentals of Veterinary Practice (FVP), and Veterinary Research and Evidence-based Veterinary Medicine (VREBVM). In the perception study, 79.6% of students felt that their preparation for OTSPAs drove an understanding and learning of topics that formed part of the module learning outcomes. Only a small group (21.4%) reported the assessment to be enjoyable; however, 54.1% saw value in it being an authentic assessment, reflecting real-life situations. The majority of students felt that the OTSPA helped with improving communication skills (80.4%). There was a small but significant positive correlation between the performance in OTSPAs and the FWSA in all modules. This suggests that OTSPAs can be useful in predicting the outcomes of the FWSA and, furthermore, could have utility in identifying where support may be helpful for students to improve academic performance. Outcomes from this study indicate that the OTSPA is an effective low stake summative assessment within the Surrey veterinary undergraduate programme.